Artificial Intelligence in Nigeria: A Catalyst for Economic Growth, Innovation, and Technological Advancement - Ogunbodede, Kolawole Francis; Atchrim, Imade Adebayo (Faculty of Natural and Applied Sciences Journal of Computing and Applications, 2025)
Artificial Intelligence (AI) can transform several sectors in Nigeria, with a swiftly rising population and a flourishing digital economy. With 164 million Internet users and 219 million mobile phone subscribers as at the first quarter of the year 2024, Nigeria presents a fertile ground for AI-driven innovations across various sectors and addresses key challenges, including food security, health care, education, financial inclusion, and infrastructure development. This study investigates Nigeria’s current state of AI adoption, the potential and application of AI across various sectors, and the challenges hindering the adoption of AI in Nigeria. It also looked at the roles of government programs, research institutes and private organizations in promoting AI innovation. However, despite these, some challenges are clearly evident, such as limited infrastructure, a shortage of skilled professionals and a lack of set rules and regulations. Nigeria has significant potential to harness AI for economic growth and development. The paper highlighted the need for strategic investing in AI infrastructure, AI research funding, education and developing policies that ensure ethical and responsible AI deployment. With proper implementation, AI has the potential to drive economic growth, improve public services, and enhance overall societal development, positioning Nigeria as a leader in AI-driven innovation in Africa.